Pacientes pediátricos com COVID-19: perfis clínicos e epidemiológicos e estratégias de suporte ventilatório: revisão narrativa - Modesto, Thais Silva Frota Cavalcante (2021)
Assistance to pediatric patients has greatly improved in recent years, increasing the number of hospitalizations and invasive ventilatory support for these patients, whose main indication is respiratory failure. To manage the invasive mechanical ventilation is challenging in children due to their anatomophysiological specificities. We are experiencing a pandemic due to the new coronavirus and this is yet another challenge for a child population, as there is still little information about the disease in children and adolescents, as well as the ventilation strategies to be adopted. The present study aimed to describe, through a review of the narrative-type literature, the clinical and epidemiological profiles and the main ventilation strategies adopted in the large treatment centers that received pediatric patients with important or severe Covid-19. Methodology: Narrative review study conducted between August and October 2020, in the databases Pubmed, Scielo and Lilacs. Original articles published in 2020 on covid-19 in the pediatric population were included. Results: Five articles from large pediatric centers that treated children and adolescents infected with Sars-Cov-2 were included. Most children are asymptomatic or mild to moderate, with a predominance of males. Common symptoms are fever and signs of upper airways infection. The main respiratory complication is Acute Respiratory Discomfort Syndrome (ARDS). Conclusion: The severity of covid-19 is less in the pediatric population. Patients with severe symptoms usually have comorbidities. Those who will need invasive mechanical requirements with ARDS. There are very few studies describing the ventilation strategy adopted.